Conceptual Structure of Lodging-Context Studies: 1990-2016. (May 2019) - Köseoglu, Mehmet Ali; Okumus, Fevzi; Putra, Eka Diraksa; Yildiz, Mehmet; Dogan, Ismail Cagri
The purpose of this article is to analyze the conceptual structure of lodging-context research. In this regard, 2, 632 articles published between 1990 and 2016 were analyzed utilizing network analyses. We find that the knowledge domain of lodging has been expanding, with greater focus on the business and economic activities of hotels. As the network density is low, lodging as a field is at a relatively early growth level and it is open for multidisciplinary collaborations. Articles related to strategy, marketing, and human resource management are relatively mature and well developed. However, some areas such as resource-based view, and cruise business still remain undeveloped and immature. Moreover, as one of the first studies in this field, this work provides an inclusive evaluation of the results, limitations, and suggestions for future research.